Trends in Foodborne Illness Outbreaks in Shinjuku City, Tokyo in FY2023 and Public Health Considerations - Kashiwagi, Yoshiyuki (Global Indonesia Health Care (GOICARE), 2025)
Background: Foodborne illnesses continue to pose a significant public health challenge in urban areas with active food service industries. Seasonal trends, food handling practices, and dietary behaviors influence outbreak patterns. Purpose: This study investigates foodborne illness outbreaks in Shinjuku City, Tokyo, during fiscal year 2023, focusing on causative agents, seasonality, and outbreak settings to inform targeted public health interventions. Methods: Outbreak data reported by Shinjuku City in 2023 were analyzed by month, pathogen type, and outbreak location. Administrative responses were also reviewed. All data were anonymized and ethically managed. Results: A total of 11 outbreaks involving 37 patients were reported, corresponding to an incidence rate of 10.59 per 100,000 population, the highest in the past five years. The most common causative agent was Campylobacter, followed by norovirus, Anisakis, and natural plant toxins. Most outbreaks occurred in restaurants. A clear seasonal pattern was observed, with peaks in winter and summer. Business suspensions were the most frequent administrative penalty. Conclusion: Despite ongoing public health efforts, foodborne illnesses remain a concern in Shinjuku City. Strengthened guidance for food establishments and targeted awareness campaigns, particularly for young singles and recent residents, are recommended. Special attention should be given to hygiene in game meat handling and safe food practices in households.